Implementasi Logika Fuzzy Pada Penentuan Karakteristik Teknik Disain Perancangan Produk Mainan Anak - Suhartini, Nanih (Universitas Gunadarma, 2014)
Intergrated design toys requires estimations from various parties who have interest in kids’ toys. The estimations are variables and attributes of kids’ toys, determining the technical characteristics, and providing the prior picture of technical characteristics and prior attribute which have to be met in accordance with costumers’ demands and needs. The method used to interpret the customers’ demands in a product is Fuzzy Quality Function Deployment (Fuzzy QFD). The method is able to synchronize between what customer’s demand with what they able to provide. Based on the result of the analysis, the variable of costumer’s demand of kids’ toys product consists of five main variables of customer’s demand characteristics of the kids’ toys namely forms, size, materials, benefits, and benefits of the toys. To meet the customer’s demands, it needs technical requirements, namely productive, kids’ idea-expressible, responsive, image, knowledge improvable, imaginative, communicative, and flexible. From the seven characteristics, there is a prior scale to improve the characteristics, namely responsive, image, kids’ idea-expressible, imaginative, knowledge improvable, flexible, and communicative.Keywords: Fuzzy Logic, technical characteristics, kids’ toy.